2022
DOI: 10.1021/acsaelm.2c01342
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Contact Resistance and Effective Channel Length of Thin Film Transistors Using Composition-Modified In–Ga–Zn-O Active Channels Prepared with Atomic Layer Deposition and Various Electrode Materials

Abstract: To verify the effects of process conditions for the TFTs employing In−Ga−Zn-O (IGZO) channels prepared by atomic layer deposition (ALD), such as cationic composition of channel and/or source/drain (S/D) electrodes, the device characteristics including the field-effect mobility (μ FE ), the contact resistance (R C ), and the channel length deviation (ΔL) were systematically investigated for the ALD IGZO thin film transistors (TFTs) fabricated with controlling the ALD subcyclic ratios and with variations in S/D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…Amorphous oxide semiconductors (AOSs) with extremely low off-currents originating from their electronic structure have attracted considerable interest for applications in the storage chip industry, enabling the development of capacitorless dynamic random-access memory (DRAM) architecture and high-density DRAM technologies. In contrast to thin-film transistors (TFTs) for flat panel displays, storage chips employ vertically stacked complex device architectures to achieve higher device density, posing challenges in electrode processing, and increasing the importance of contact issues between AOSs and electrodes. Process-derived poor contacts and a substantial Schottky barrier resulting from the intrinsic energy level mismatch between the work function of the electrode metal and the electron affinity of AOSs eventually lead to excessively high contact resistance ( R C ), thereby degrading field-effect mobility and power consumption. Recently, many works have proposed methods to solve high contact resistance between AOSs and metal electrodes, which may be categorized into several main strategies: additional deposition of a highly conductive oxide interlayer, oxidation of the metal contact surface resulting in the formation of high concentration oxygen vacancies on the AOS contact surface via high-temperature annealing, penetration of metal ions into the AOS layer, , and surface treatment with plasma. These methods, which involve high-energy or multistep processes, offer effective solutions for the high contact resistance of the exposed upper surface of oxide semiconductors, as shown in Figure a, but are almost impossible to apply to buried contact or deep vertical interfaces within nanoscale complex structures.…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous oxide semiconductors (AOSs) with extremely low off-currents originating from their electronic structure have attracted considerable interest for applications in the storage chip industry, enabling the development of capacitorless dynamic random-access memory (DRAM) architecture and high-density DRAM technologies. In contrast to thin-film transistors (TFTs) for flat panel displays, storage chips employ vertically stacked complex device architectures to achieve higher device density, posing challenges in electrode processing, and increasing the importance of contact issues between AOSs and electrodes. Process-derived poor contacts and a substantial Schottky barrier resulting from the intrinsic energy level mismatch between the work function of the electrode metal and the electron affinity of AOSs eventually lead to excessively high contact resistance ( R C ), thereby degrading field-effect mobility and power consumption. Recently, many works have proposed methods to solve high contact resistance between AOSs and metal electrodes, which may be categorized into several main strategies: additional deposition of a highly conductive oxide interlayer, oxidation of the metal contact surface resulting in the formation of high concentration oxygen vacancies on the AOS contact surface via high-temperature annealing, penetration of metal ions into the AOS layer, , and surface treatment with plasma. These methods, which involve high-energy or multistep processes, offer effective solutions for the high contact resistance of the exposed upper surface of oxide semiconductors, as shown in Figure a, but are almost impossible to apply to buried contact or deep vertical interfaces within nanoscale complex structures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, by using the electrical characteristics of a-IGZO that change according to the oxygen vacancy ratio, the performance of the device was improved by adjusting the carrier concentration of the channel to form an Ohmic contact, and there was also an experiment in which the performance of the device was improved by inserting an interlayer of high carrier concentration between the channel and the electrode. Lee et al reported the impact of contact resistance on the performance of IGZO TFTs fabricated by ALD with modulated semiconductor composition and two types (ITO and Mo) of S/D electrodes. …”
Section: Introductionmentioning
confidence: 99%
“…However, these methods can damage the channel layer below the S/D electrodes, which increases the interface defects and offsets the merits of increasing n c . In addition to these doping techniques, other approaches such as controlling cation composition, metal-induced oxygen scavenging and highly conductive interlayer (IL) insertion have been employed [22][23][24][25][26][27]34,35 . These methods have an advantage in that they can reduce the barrier width without incurring damage.…”
mentioning
confidence: 99%